Manajemen Risiko dalam Proyek Konstruksi Studi Kasus Evaluasi dan Rekomendasi Proyek Konstruksi Perumahan PT Dharma Sakti - Doni Hartono; Anjar Safitri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research focuses on identifying and analyzing risks that can affect the implementation of housing construction projects in response to increasing population. A survey method using a questionnaire was used to collect data from stakeholders regarding housing construction projects. The results of risk identification based on events and consequences show that K3L and bureaucratic, natural and information aspects are high risks based on events, while social and location, external, planning and implementation management aspects are significant risks based on events. Based on consequences, natural aspects and government policies are considered high risk, while social, location and internal aspects are considered significant risk. Principal Component Analysis (PCA) confirmed these findings. The implications of the results of this research include the need to adopt proactive strategies in risk management, strengthening capacity in dealing with critical risks, government involvement in addressing policy and natural risks, as well as emphasizing social and location aspects in planning and implementing housing construction projects. These findings can serve as a basis for improving risk management in the context of uncertainty in the implementation of residential construction projects and the development of more effective industrial policies.